2022
DOI: 10.3390/ijms231911379
|View full text |Cite
|
Sign up to set email alerts
|

Dystocic Labor and Adrenergic and Noradrenergic Neurotransmitters: A Morphological Experimental Study

Abstract: Authors investigated the catecholaminergic neurotransmitters (chNs) quantitative modifications in pregnant uterine Lower Uterine Segment (LUS) during prolonged labor (PL) with the fetus in an occiput-posterior position (OPP), in occiput transverse position (OTP) and in fetal head asynclitism, all diagnosed by Intrapartum Ultrasonography (IU). The chNs neurotransmitters, particularly adrenaline (or epinephrine-A) and noradrenaline (or norepinephrine-N), were evaluated in LUS fragments sampled during CS of 34 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Thus, epinephrine and norepinephrine can stimulate, alter, and regulate myometrial activity in humans, although their physiologic and therapeutic importance is doubtful [ 54 ]. Malvasi et al showed, in the dystocic prolonged labor, a reduction in adrenergic and noradrenergic neurofibers, determining an alteration in the vascularization of the LUS and, consequently, uterine contractility [ 55 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, epinephrine and norepinephrine can stimulate, alter, and regulate myometrial activity in humans, although their physiologic and therapeutic importance is doubtful [ 54 ]. Malvasi et al showed, in the dystocic prolonged labor, a reduction in adrenergic and noradrenergic neurofibers, determining an alteration in the vascularization of the LUS and, consequently, uterine contractility [ 55 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hu et al [ 25 ] demonstrated that fetal distress is associated with endogenous opioids, measuring concentrations of plasmatic endogenous opioid neuropeptides (EOP), such as beta-endorphin, endorphin A [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ], and leu-enkephalin, measured by radioimmunoassay. They detected that the modifications in EOP levels in umbilical artery may play an important role in fetal distress, in the pathophysiological changes [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Malvasi et al [ 2 , 3 ] demonstrated the presence of neuro fibers and neurotransmitters in the Lower Uterine Segment (LUS), in the uterine scar in greater density. Moreover, Malvasi et al [ 4 ] showed that in Prolonged Dystocic Labor (PDL) there is a reduction in adrenergic and noradrenergic neuro fibers and neurotransmitters in the LUS.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of dystocia and the tensile characteristics and changes of the LUS in previous caesarean scars were documented by Buhimschi et al [6] . Malvasi et al revealed that in the PDD there is a morphometric reduction of adrenergic fibers, evaluated by SEM and FM [7] , and of enkephalinergic neurofibers in comparison to non-progressive dystocic labor (NPDD) [8] . This study investigated, by SEM and FM, the presence of oxytocinergic Nfc in NPDD and PDD during cesarean section (CS).…”
Section: Introductionmentioning
confidence: 99%